A Multicenter Study of Noninvasive Wireless Assessment of Cerebrospinal Fluid Shunt Function in Hydrocephalus Patients - Limbrick, Jr, David D; Skoch, Jesse; Auguste, Kurtis; Grant, Gerald A; Lam, Sandi K; Tate, Matthew C; Langer, David J; Roland, Jarod L; Alden, Tord D; Charbel, Fady T; Lober, Robert M; Patten, Keith; et al. (Neurosurgery, 2025)
Diagnosis of cerebrospinal fluid (CSF) shunt failure is complex, relying on a combination of patient symptoms, history, and indirect tests, in part due to the inability to easily access information about shunt function. The objective of this study was to evaluate the performance of a novel noninvasive wearable wireless device in assessing the presence of shunt flow in patients presenting with possible shunt failure. This was a prospective validation study including patients with an existing implanted CSF shunt system and symptoms of possible shunt failure. Subjects underwent evaluation with the study device in addition to standard-of-care evaluation. Device measurement data were evaluated with 2 algorithms and classified as "flow confirmed" or "flow not confirmed." Subjects were followed for 7 days and, in patients undergoing shunt surgery, intraoperative assessment of shunt functionality established the presence or absence of complete shunt failure. Additional subjects were enrolled for user training and algorithm development. In total, the study device was used on 182 subjects for user training, algorithm development, and validation. The final algorithm validation data set included 112 subjects. The random forest algorithm outperformed the binary threshold algorithm. The sensitivity of the random forest algorithm (correct identification of complete shunt failure) was 88.9%, and the specificity (correct identification of an absence of complete shunt failure) was 49.2% with a negative predictive value of 96.8%. This study established the performance of a first-generation wearable thermal anisotropy sensor in the identification of CSF shunt flow in symptomatic patients. The high negative predictive value suggests potential application to identify flowing shunts. Additional device performance and clinical outcome studies are underway.